The One, the Three, and the many : God, creation, and the culture of modernity - Gunton, Colin E. (Cambridge ; New York, NY, USA : Cambridge University Press, 1993)
This study, based on the Bampton Lectures delivered in the University of Oxford in 1992, examines what is often called the crisis of modernity, with reference not only to modernity but to modern culture in general. Problems of social, theological, and philosophical thought are traced back beyond the Enlightenment to the very roots of Western Christian theology. A response to these problems is essayed by constructively developing conceptual possibilities to be found in ancient and modern theology of the Trinity.
pt. 2. Rethinking createdness. The universal and the particular : towards a theology of meaning and truth. Foundationalism and rationality ; The one as transcendental ; The open transcendental ; Trinitarian transcendentals -- 'Through whom and in whom ... ' : towards a theology of relatedness. Recapitulation ; Economy ; Perichoresis ; An analogical exploration ; The heart of the problem ; Christological conclusion -- The Lord who is the Spirit : towards a theology of the particular. The concept of spirit ; The problem of substantiality ; Of particulars ; The lord and giver of being -- The triune Lord : towards a theology of the one and the many. Recapitulation ; Community ; Sociality ; Sociality in context ; Conclusion.
"The Bampton lectures, 1992."
Includes bibliographical references (p. 232-240) and index.
Keywords: Theology; Christianity and culture; Trinity -- History of doctrines -- 20th century; Modernism (Christian theology)